Genotype-phenotype correlation in Costello syndrome: HRAS mutation analysis in 43 cases. Issue 5 (27th January 2006) - Kerr, B; Delrue, M-A; Sigaudy, S; Perveen, R; Marche, M; Burgelin, I; Stef, M; Tang, B; Eden, O B; O'Sullivan, J; De Sandre-Giovannoli, A; Reardon, W; et al.
Abstract : Background: Costello syndrome (CS) is a rare multiple congenital abnormality syndrome, associated with failure to thrive and developmental delay. One of the more distinctive features in childhood is the development of facial warts, often nasolabial and in other moist body surfaces. Individuals with CS have an increased risk of malignancy, suggested to be about 17%. Recently, mutations in the HRAS gene on chromosome 11p13.3 have been found to cause CS. Methods: We report here the results of HRAS analysis in 43 individuals with a clinical diagnosis of CS. Results: Mutations were found in 37 (86%) of patients. Analysis of parental DNA samples was possible in 16 cases for both parents and in three cases for one parent, and confirmed the mutations as de novo in all of these cases. Three novel mutations (G12C, G12E, and K117R) were found in five cases. Conclusions: These results confirm that CS is caused, in most cases, by heterozygous missense mutations in the proto-oncogene HRAS. Analysis of the major phenotypic features by mutation suggests a potential correlation between malignancy risk and genotype, which is highest for patients with an uncommon (G12A) substitution. These results confirm that mutation testing for HRAS is a reliable diagnostic test for CS.